Modern Science Parks: Moving From Property Management to Become Knowledge Organisations Orchestrating Regional Innovation Systems - Justyna DĄBROWSKA; Iryna MANCZAK (Communications of International Proceedings, 2025)
This study aims to examine the evolving role of science parks within regional innovation systems while critically engaging with and challenging existing scholarly perspective. Traditionally regarded as spaces supporting technology transfer, science parks have undergone a significant transformation, emerging as key knowledge facilitators among enterprises, academic institutions, and governmental bodies. Since scholarly discourse on the changing function of science parks as knowledge organisations remains scarce, this study seeks to address a critical gap by analysing their transformation. The motivation behind this study stems from the need to reassess the role of science parks beyond their traditional functions and recognise their contribution as knowledge organisations actively shaping regional innovation dynamics. The selected research methodology, integrating desk research and critical analysis, combined foundational insights from secondary sources with a deeper evaluation of prevailing perspectives. The findings of this study highlight the significant evolution of science parks, providing evidence that they have transitioned into knowledge organisations playing a crucial role in orchestrating regional innovation systems. By exhibiting core attributes of knowledge organisations—such as the ability to systematically collect, process, and disseminate knowledge in various forms as demonstrated in the study—science parks have moved beyond their traditional role as providers of physical infrastructure. Given an increasing role of science parks in innovation systems, this phenomenon holds substantial implications for regional development and long-term economic sustainability. The article offers valuable insights for policymakers and encourages further academic inquiry into the ways modern science parks operate as pivotal contributors to regional innovation systems.
Keywords: science parks; innovation services; innovation systems; knowledge organisations; concept of ‘ba’